Mass Casualty Triage and Tagging Scenario in the Pre-hospital Setting Simulated Event - Paul Y. Ko; Shaunna L. Escobar; Harry J. Wallus; McKenna J. Knych; Anthony S. Rossettie; Christopher A. Dunham; Jay M. Scott (Association of American Medical Colleges, 2012)
Abstract This Mass Casualty Simulation Event was started and designed by medical students from the Emergency Medicine Interest Group in conjunction with our emergency medicine service fellows. It teaches students the essential tips and tools needed to triage, assess, and stabilize patients during a mass casualty event. We have been doing this event for at least the last 4 years with great enthusiasm from the participants. The module includes a simulation scenario file, an instructor's guide, a PowerPoint presentation, images, basic tips, and an evaluation form. The total time to run the scenario is approximately 3 hours. Organized by students within the organization, it was put on with the assistance of emergency medicine faculty, residents, and fellows. The target audience were first- through fourth-year medical students. This past year, survey and feedback were collected from the participants of the event. Thirteen participants responded to the feedback form giving the exercise an average rating of 9.3 out of 10. Limitations to full implementation of this curriculum are mostly financial and time constraints. The professional moulage kits used are not inexpensive, but worthy investment. There are also less expensive ways to moulage patients, as instructed in the moulage basics & tips supplemental sheet. Additionally, recruiting enough actors for the scenario is also important and not always possible.